2009
DOI: 10.1007/s00394-008-0772-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum nutrients and habitual dietary intake in colectomized FAP patients in Norway

Abstract: We would suggest that the nutrient intake among FAP patients should at least meet the recommendations for healthy subjects. Their risk of metachronous cancers should also cause special attention to dietary factors that may prevent nutritional deficiency and carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The intake of omega-3 fatty acids was lower than the minimum recommendation of 0.5% of energy in the patients not taking omega-3 supplements [41, 42]. Notably, cancer patients are generally advised to take supplements with very long chain omega-3 fatty acids, and to follow the general dietary guidelines [43].…”
Section: Discussionmentioning
confidence: 99%
“…The intake of omega-3 fatty acids was lower than the minimum recommendation of 0.5% of energy in the patients not taking omega-3 supplements [41, 42]. Notably, cancer patients are generally advised to take supplements with very long chain omega-3 fatty acids, and to follow the general dietary guidelines [43].…”
Section: Discussionmentioning
confidence: 99%
“…The main dietary-source of arachidonic acid is animal products. However, the dietary assessment showed that the intake of such foods was normal among these familial adenomatous polyposis patients [18]. …”
Section: Discussionmentioning
confidence: 99%
“…In the ileostomy group, levels of total cholesterol were negatively correlated to the content of palmitic acid, palmitolic acid, stearic acid, oleic acid, linoleic acid, and monounsaturated fatty acids (<18 C atoms) in feces, which is interesting since the present levels of total cholesterol are lower than those among a healthy reference group [18]. In the ileal-pouch-anal anastomosis group separately, the content of monounsaturated fatty acid in feces was positively correlated to dietary intake of monounsaturated fatty acids in particular.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations